Wealth and Prosperity Gospel: Challanges to Christianity in Igboland - Nwokocha, Benjamin C. (SIST journal of religion and humanities, 2022)
The research work ventured into the impacts of Christianity in Igboland. Following the way and manner Christianity is being practiced after the many years of Christians’ presence in Igboland, it has left one to wonder whether the said Christian religion has firmly been rooted in the hearts of the people. It is an obvious fact that the major achievements of Christianity in Igboland since its inception in are the unbridled proliferations of churches, inter-denominational migration and insatiable quest for prosperity amongst some Christians. The incessant rise in churches especially the group known as “Pentecostals” have instead of promoting the good moral values have rather increased jealousy, unhealthy competitions, wickedness, and other social vices due to an excessive desire for wealth and materialism. Of late, the issue of wealth and prosperity has become almost synonymous with Christian religious practice as if that is the only rewards for devout religious observance. These are the reasons why the researcher thinks there is a need to x-ray and analyze the impacts of Christianity in Igboland so as to address some issues that does not portray the church in a lime light. Specifically, the research work examined the impact of prosperity gospel in promoting a high desire for wealth and materialism. The findings of this research discovered that a lot of evil and atrocities are committed in the name of prosperity and get-wealth-quick syndrome. Generally, in the contemporary Nigerian Pentecostalism, there are rampart corruption, diabolism, and moral decadence in the name of invoking wealth for the followers. The core objective of this study is therefore to examine the Christian religious activities in Igboland especially the group known and addressed as the Pentecostal churches. The method of approach is historical and descriptive nature method of research with the primary and secondary sources of data collection.
free